2011
DOI: 10.1007/s12288-011-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Childhood Idiopathic Myelofibrosis in Down’s Syndrome: A Case Report

Abstract: Idiopathic myelofibrosis a disease of elderly is rarely seen in children. A case of chronic idiopathic myelofibrosis in an 8 year old boy with Down's syndrome is reported here, who presented with progressive pallor and hepatosplenomegaly. Peripheral blood examination revealed pancytopenia, macrocytic anemia and tear drop cells. No blasts were found. Bone marrow aspirate yielded a dry tap and trephine biopsy showed marrow fibrosis with osteosclerosis. Focally megakaryocytes were increased in number with atypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…Following reasons may correlate with relatively unfavorable outcomes of childhood patients with PMF in our cohort. Firstly, the onset age of our patients appeared to be older than previous reports . Secondly, none of our patient accepted HSCT, compared with that nearly half of patients accepted HSCT in the previous report .…”
Section: Disscussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Following reasons may correlate with relatively unfavorable outcomes of childhood patients with PMF in our cohort. Firstly, the onset age of our patients appeared to be older than previous reports . Secondly, none of our patient accepted HSCT, compared with that nearly half of patients accepted HSCT in the previous report .…”
Section: Disscussioncontrasting
confidence: 75%
“…It was found that in adult patients with PMF the frequency of JAK2 V617F mutations was approximately 50% [3,5] and the frequency of MPL W515K/L mutations was 5-10% [4,5]. But PMF is quite rare in children, for only 33 cases of pediatric patients with PMF reported in the literatures until now [6][7][8][9][10][11][12][13]. In the largest series [12], none of 19 patients had mutations in JAK2 V617F or MPL W515K/L , a striking contrast to adult patients with PMF.…”
Section: Introductionmentioning
confidence: 99%
“…Although our series suggests that the majority of MF cases have a benign course with spontaneous resolution, one patient (Pt10) affected by Down Syndrome after being diagnosed with PedIMF, subsequently developed malignant evolution (Acute myeloblastic leukemia). Although the relationship between trisomy 21 and MF has been already described (17,18) this association can be only speculated due to lack of data.…”
Section: Discussionmentioning
confidence: 98%